2014
DOI: 10.1007/s40620-013-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Early stage of obesity potentiates nitric oxide reduction during the development of renal failure

Abstract: The early changes in NO metabolism are associated with an early stage of obesity. This effect on NO potentiates kidney damage development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It has been widely reported that oxidative stress is implicated in a variety of physiological and pathological processes that include aging, cancer, diabetes, and atherosclerosis [ 46 ], and plays an important role in the development of endothelial dysfunction and vascular diseases [ 20 , 47 , 48 ]. Hence, an important possible mechanism associated with the decreased NO and PGI 2 bioavailability in obese mice observed in this study might be the presence of increased ROS/RNS in vascular tissue, as suggested by a previous study from our laboratory [ 10 ]. In the same manner, endothelium-dependent contractions were abolished by superoxide dismutase in canine basilar artery [ 49 ].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It has been widely reported that oxidative stress is implicated in a variety of physiological and pathological processes that include aging, cancer, diabetes, and atherosclerosis [ 46 ], and plays an important role in the development of endothelial dysfunction and vascular diseases [ 20 , 47 , 48 ]. Hence, an important possible mechanism associated with the decreased NO and PGI 2 bioavailability in obese mice observed in this study might be the presence of increased ROS/RNS in vascular tissue, as suggested by a previous study from our laboratory [ 10 ]. In the same manner, endothelium-dependent contractions were abolished by superoxide dismutase in canine basilar artery [ 49 ].…”
Section: Discussionmentioning
confidence: 61%
“…Roberts, et al (2000) found a decline in urinary nitrites and a significant raise in nitrotyrosine, a hallmark of NO inactivation by ROS, in aorta from rats fed for 24 months with a high-fat, refined carbohydrate diet [ 9 ]. Recently, we demonstrated in a diet induced obesity mouse model, that 2 weeks on a high fat diet are enough to increase superoxide anion levels in kidney tissue and to decrease urinary NO metabolites associated with a reduction in plasma tetrahydrobiopterin (BH4) concentration [ 10 ]. These changes were prevented by an antioxidant plus L-arginine treatment, suggesting that inactivation of endothelium nitric oxide synthase (eNOS) and the subsequent diminishment in NO bioavailability was related to the sequestration of NO by ROS and the uncoupling of eNOS by reduction in BH4 availability during obesity.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether a HFD induces MetS in our experimental setting, we measured the metabolic parameters body weight, fasting blood glucose, and triglycerides over a period of eight weeks starting at an age of 5 weeks ( Figure 1 ). In a previous study, we investigated the effects of early obesity on kidney damage and observed that a two-week period of HFD was not sufficient to induce MetS since at this time point triglyceride and glucose plasma levels and blood pressure were not yet altered significantly [ 16 ]. Our current time course confirmed these previous findings since, two weeks after starting the respective diets, we did not observe statistically significant differences for body weight ( Figure 1(a) ), blood glucose ( Figure 1(b) ), and triglycerides ( Figure 1(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the fact that the antioxidative vitamins C and E as well as the NO source L-arginine have been shown to ameliorate obesity-induced kidney damage and CVD risk factors [ 4 , 16 , 18 ], we wanted to know whether a combination of these micronutrients in the formula corabion given by daily gavage during the whole experimental procedure could reverse obesity-induced CVD risk factors in mice. As expected, antioxidative treatment did not affect the gain in body weight over the experimental period of 8 weeks ( Figure 1(a) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation